2009
DOI: 10.1002/mus.21295
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electromyographic responses for the superficial quadriceps muscles: Cycle versus knee‐extensor ergometry

Abstract: The purpose of this study was to compare the electromyographic (EMG) amplitude and mean power frequency (MPF) versus power output relationships for the three superficial quadriceps muscles during incremental cycle (CE) and knee-extensor (KE) ergometry in the same subjects. Eight men performed incremental CE and KE tests to exhaustion. Surface EMG signals were recorded simultaneously from the vastus lateralis (VL), rectus femoris (RF), and vastus medialis (VM). Polynomial regression analyses on a subject-by-sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 23 publications
(86 citation statements)
references
References 37 publications
(71 reference statements)
4
82
0
Order By: Relevance
“…The single-leg KE exercise paradigm has been described previously (Richardson et al, 1995(Richardson et al, , 1998, but it was modified for two-legged exercise (Koga et al, 2005;Malek et al, 2009) for the present study (Fig. 1).…”
Section: Maximal Knee-ergometer (Ke) Testmentioning
confidence: 99%
See 4 more Smart Citations
“…The single-leg KE exercise paradigm has been described previously (Richardson et al, 1995(Richardson et al, , 1998, but it was modified for two-legged exercise (Koga et al, 2005;Malek et al, 2009) for the present study (Fig. 1).…”
Section: Maximal Knee-ergometer (Ke) Testmentioning
confidence: 99%
“…For KE, however, the patterns of responses for EMG amplitude versus power output were best-fit with a linear model for the composite data as well as for each subject for all three muscles. In addition, Malek et al (2009) reported that the EMG amplitude was higher (p < 0.05) for both the rectus femoris and vastus medialis muscles during KE incremental exercise when compared to CE. The investigators (Malek et al, 2009), therefore, concluded that KE exercise was a more optimal measure and better representation of quadriceps muscle activity than CE exercise.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations